Early Motherhood and Contraceptive Use among Adolescents: A Study from Rajshahi District of Bangladesh - Rahman, Md Mosiur (Journal of Nepal Paediatric Society, 2009)
Introduction: This paper employs various statistical methods to identify the factors associated with age at first motherhood and contraception use among the adolescence mothers in Rajshahi district of Bangladesh. Methods: To meets the objectives this study utilizes information from 1000 married adolescents of Rajshahi district within the age span (15-19 years). Results: We have observed adolescents mean age at first marriage and birth to be 15.0 and 16.4 years. This study reveals that the education, place of residence, occupation of husband and religion played the greatest roles on adolescent's age at first motherhood. The analysis shows that, use of contraceptive among the adolescent's was still very low. Slightly 56.7 per cent of the married adolescents were currently using any method of contraception. Among the factors determining contraceptive use among adolescents, education, visits of family planning workers and place of residence appears to be the most significant and positively associated with contraceptive use. Conclusions: The results indicate several policy options: (1) government has to take initial steps to strictly prohibit the early marriage with the proper application of existing law that would directly or indirectly rise the age at first birth among the adolescence; (2) programmes that encourage postponement of first birth after marriage through adoption of temporary contraceptive methods should be considered seriously ; (3) provide adolescents with information on the availability of family planning methods and their effectiveness; (4) increase the number of visits by family planning workers and their counseling about family planning methods help to motivate adolescents to accept family planning methods and use them effectively and (5)emphasize adolescents education to make a lasting impact on overall health of the adolescent mothers. Key words: Adolescence, age specific live birth, contraception DOI: 10.3126/jnps.v30i1.2454 Journal of Nepal Paediatric Society Vol.30(1) 2010 8-17